Trends in seabird breeding populations across the Great Barrier Reef. Issue 3 (13th January 2021) - Woodworth, Bradley K.; Fuller, Richard A.; Hemson, Graham; McDougall, Andrew; Congdon, Bradley C.; Low, Matthew
Abstract: The Great Barrier Reef is an iconic ecosystem, known globally for its rich marine biodiversity that includes many thousands of tropical breeding seabirds. Despite indications of localized declines in some seabird species from as early as the mid‐1990s, trends in seabird populations across the reef have never been quantified. With a long history of human impact and ongoing environmental change, seabirds are likely sentinels in this important ecosystem. Using 4 decades of monitoring data, we estimated site‐specific trends for 9 seabird species from 32 islands and cays across the reef. Trends varied markedly among species and sites, but probable declines occurred at 45% of the 86 species‐by‐site combinations analyzed compared with increases at 14%. For 5 species, we combined site‐specific trends into a multisite trend in scaled abundance, which revealed probable declines of Common Noddy (Anous stolidus), Sooty Tern (Onychoprion fuscatus), and Masked Booby (Sula dactylatra), but no long‐term changes in the 2 most widely distributed species, Greater Crested Tern (Thalasseus bergii) and Brown Booby (Sula leucogaster). For Brown Booby, long‐term stability largely resulted from increases at a single large colony on East Fairfax Island that offset declines at most other sites. Although growth of the Brown Booby population on East Fairfax points to the likely success of habitat restoration on the island, it also highlights a general vulnerability wherein large numbers of some species are concentrated at a small number of key sites. Identifying drivers of variation in population change across species and sites while ensuring long‐term protection of key sites will be essential to securing the future of seabirds on the reef. Abstract : Article Impact Statement: Four decades of monitoring reveals troubling trends for seabird breeding populations across the Great Barrier Reef. Abstract : Tendencias en las Poblaciones de Aves Marinas Reproductoras a lo largo de la Gran Barrera de Arrecifes Resumen: La Gran Barrera de Arrecife es un ecosistema icónico, conocido mundialmente por la riqueza de biodiversidad marina que incluye a miles de aves marinas tropicales en reproducción. A pesar de las indicaciones de la declinación localizada de algunas especies de aves marinas que datan desde tan temprano como mediados de la década de 1990, nunca se han cuantificado las tendencias de las poblaciones de aves marinas a lo largo del arrecife. Con una larga historia de impacto antropogénico y el cambio climático en curso, las aves marinas son los probables centinelas de este importante ecosistema. Usamos cuatro décadas de datos de monitoreo para estimar las tendencias específicas de sitio para nueve especies de aves marinas en 32 islas y cayos en todo el arrecife. Las tendencias variaron notablemente entre especies y sitios, aunque las declinaciones probables ocurrieron en 45% de las 86 combinaciones de especie por sitio analizadas en comparación con los incrementos al 14%. Combinamos las tendencias específicas de sitio para cinco especies con una tendencia multisitio con abundancia escalada. Lo anterior reveló declinaciones probables para las siguientes especies: Anous stolidus, Onychoprion fuscatus y Sula dactylatra, pero ningún cambio a largo plazo para las dos especies con mayor distribución: Thalasseus bergii y Sula leucogaster. Para Sula leucogaster, la estabilidad a largo plazo resultó principalmente de los incrementos en una gran colonia única en la isla Fairfax del Este, la cual compensó las declinaciones en casi todos los demás sitios. Aunque el crecimiento de la población de Sula leucogaster en la isla Fairfax del Este apunta hacia el éxito probable de la restauración del hábitat en la isla, también resalta una vulnerabilidad general en la que los grandes números de algunas especies están concentrados en un número reducido de sitios importantes. La identificación de los causantes de la variación en los cambios poblacionales en las especies y en los sitios mientras se asegura la protección a largo plazo de los sitios importantes será esencial para asegurar el futuro de las aves marinas del arrecife. 【摘要】: 大堡礁是一个具有标志性的生态系统, 以其丰富的海洋生物多样性闻名于世, 其中包括成千上万的热带繁殖海鸟。尽管早在 20 世纪 90 年代中期就存在一些海鸟局部种群下降的迹象, 但大堡礁范围内海鸟数量的总体趋势从未得到量化。由于人类的长期影响和持续的环境变化, 海鸟很可能是这个重要生态系统的指示物种。本研究利用长达 40 年的监测数据, 估计了大堡礁范围内 32 个岛屿和沙洲的 9 种海鸟在每个位点的种群变化趋势。结果显示, 不同物种和不同位点的变化趋势存在很大差异, 但在 86 个物种–位点组合中, 有 45% 可能呈现下降趋势, 而上升的比例仅为 14%。我们还对 5 个物种的海鸟进一步整合了单位点和多位点相对丰度的数据, 发现白顶玄鸥 ( Anous stolidus) 、乌燕鸥 ( Onychoprion fuscatus) 、蓝脸鲣鸟 ( Sula dactylatra) 种群都可能在减少, 但两种广泛分布的鸟类, 大凤头燕鸥 ( Thalasseus bergii) 和褐鲣鸟 ( Sula leucogaster) 种群没有长期变化。对于褐鲣鸟来说, 长期的稳定很大程度上是由于东费尔法克斯岛单个大种群的增长抵消了其他大多数位点的种群下降。虽然东费尔法克斯岛褐鲣鸟数量的增长表明岛屿栖息地可能得到成功恢复, 但它也凸显了一些物种普遍大量集中在少数几个重要位点的脆弱性问题。确定不同物种和不同位点种群变化的驱动因素, 同时确保重要位点的长期保护, 对于守护珊瑚礁海鸟的未来至关重要。【翻译:胡怡思; 审校: 聂永刚】